Ответы и объяснения

2013-03-19T19:07:56+04:00

1) \frac{3m}{5n-5m}*\frac{m^{2}-n^{2}}{3n+3m}=\frac{3m}{5(n-m)}*\frac{(m-n)(m+n)}{3(n+m)}=\frac{m}{5};

при m=2,5: \frac{m}{5}=\frac{2,5}{5}=0,5

2) \frac{5m-n}{4m+n}*\frac{16m^{2}-n^{2}}{3n+3m}=\frac{5m-n}{4m+n}*\frac{(4m-n)(4m+n)}{3(n+m)}=\frac{(5m-n)(4m-n)}{3(n+m)}

при m=1\4, n=-3:

\frac{(5*\frac{1}{4}+3)(4*\frac{1}{4}+3)}{3(\frac{1}{4}-3)}=\frac{\frac{17}{4}*4}{-\frac{33}{4}}=-\frac{68}{33}=-2\frac{2}{33}

3) \frac{a^{2}-25}{a^{2}-3a}:\frac{a+5}{9-a^{2}}=\frac{(a-5)(a+5)(3-a)(3+a)}{a(a-3)(a+5)}=-\frac{(a-5)(3+a)}{a}

при а=1: -\frac{(1-5)(3+1)}{1}=-(-4*4)=16

4) \frac{3n^{2}-3m^{2}}{n^{2}+6n}:\frac{6m^{3}-6n^{2}m}{?+n}

в 4 непонятно написано